2017
DOI: 10.1371/journal.pmed.1002368
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of novel computerized tomography scoring systems in human traumatic brain injury: An observational, multicenter study

Abstract: BackgroundTraumatic brain injury (TBI) is a major contributor to morbidity and mortality. Computerized tomography (CT) scanning of the brain is essential for diagnostic screening of intracranial injuries in need of neurosurgical intervention, but may also provide information concerning patient prognosis and enable baseline risk stratification in clinical trials. Novel CT scoring systems have been developed to improve current prognostic models, including the Stockholm and Helsinki CT scores, but so far have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 50 publications
5
84
1
3
Order By: Relevance
“…Its accuracy has been evaluated in various studies and AUCs (in the range of 0.76-0.68) have been reported with the same pseudo-R2 11 , 12 . The Marshall Classification was based on the Traditional Coma Data Bank (TCDB) from 1987 to 1984, in which 746 patients with severe traumatic traumatic brain injury (GCS 3-8) compared with other classification systems that had the lowest pseudo- variance, adding it to the checklist for patients with traumatic brain injury in admission time does not provide any additional independent information to doctors 13 . Deepika et al (2015) in a study compared the predictive power of mortality from TBI in both Marshall and Rotterdam scoring methods, the mean grade based on the Marshall Classification and Rotterdam classifications in died patients was significantly higher than that of the live patients 14 , which is in agreement with our study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its accuracy has been evaluated in various studies and AUCs (in the range of 0.76-0.68) have been reported with the same pseudo-R2 11 , 12 . The Marshall Classification was based on the Traditional Coma Data Bank (TCDB) from 1987 to 1984, in which 746 patients with severe traumatic traumatic brain injury (GCS 3-8) compared with other classification systems that had the lowest pseudo- variance, adding it to the checklist for patients with traumatic brain injury in admission time does not provide any additional independent information to doctors 13 . Deepika et al (2015) in a study compared the predictive power of mortality from TBI in both Marshall and Rotterdam scoring methods, the mean grade based on the Marshall Classification and Rotterdam classifications in died patients was significantly higher than that of the live patients 14 , which is in agreement with our study.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Thelin et al, Showed that the accuracy of Marshall CT classification was less than the classification of Rotterdam in examining the outcomes of patients with traumatic brain injury. Thelin and colleagues have been selected unfavorable outcomes to compare them with the tools, which suggest the possibility of using the Rotterdam system to evaluate morbidity, in addition to mortality 13 . In spite of the high accuracy of the Marshall and Rotterdam classification systems, especially the Rotterdam classification system, Maas et al (2005) in a study using CT scan results of over 2500 patients with blunt trauma, has concluded that by adding some variables to these scoring systems, their performance can be improved 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A range of CT findings have been shown individually to relate to prognosis in head injury. 29,41,42,51 These have been combined in a variety of ways in different approaches to classification and scoring, and there is no consensus about a uniform system. 21,26 We were clear that for practical impact our approach needed to have clinical face value, to use a very limited number of categories to produce charts with distinctly different patterns, and to be as simple and easy to apply as possible.…”
Section: Discussionmentioning
confidence: 99%
“…To take account of these differences in recording, and in accord with their prognostic value, CT data were abstracted from the CRASH and IMPACT databases and categorized according to the presence or absence of 3 abnormalities: 1) an intracranial hematoma (evacuated or not), 2) absent cisterns, and 3) SAH. 41,51…”
Section: Ct Scanmentioning
confidence: 99%